TEACHERS’ PERCEPTION OF USING QUIZIZZ AS A FORMATIVE ASSESSMENT TOOL AT SMA NEGERI 2 AMBON - Maruanaya, Jordie; Maruanaya, Hendrik; Lekawael, Rosina (Pattimura University, 2024)
This study employed a qualitative research design to investigate how teachers use the Quizizz platform as a formative assessment tool in English foreign language (EFL) teaching, and to explore teachers' perceptions of using Quizizz. The researchers conducted a preliminary study in Ambon, to identify teachers who were using Quizizz for formative assessment. Four teachers from SMA Negeri 2 Ambon were then selected as the sample for the present study. Data was collected through semi-structured interviews. The findings reveal that the teachers demonstrated a thoughtful and structured approach to integrating Quizizz into their lessons. They strategically designed Quizizz assessments to target key language skills like vocabulary, grammar, and reading comprehension. The teachers perceived several benefits of using Quizizz, including enhanced student engagement and motivation, improved learning and comprehension, and more efficient assessment processes. However, challenges were also noted, such as the reliance on stable internet connectivity and issues of digital equity, where not all students had access to the necessary devices.